Financial flows in the field of insurance - Alieksieiev, I.; Mazur, A.; Moroz, A. (Lviv Politechnic Publishing House, 2019)
The introduction of an insurance culture in Ukraine should be based on theoretical studies in this area. The authors carried out a certain review of Ukrainian scientific publications devoted to the development of the insurance market, the analysis of the state of insurance and insurance companies, historical experience and comparative analysis of insurance activities of Ukrainian and foreign insurers. This allowed us to formulate a proposal for a research typology and supplement it. The typology of directions of insurance problems studying, which are conducted by Ukrainian scientists taking into account generalizations of foreign experience, is given. At the same time, our research direction is oriented to one segment of the insurance market, namely, health insurance. As a result of the review of scientific publications on this topic, attention was drawn to the absence of research into financial flows in Ukraine in such segment of health insurance as medical insurance for Ukrainian students studying at foreign universities. It is well-known that Ukrainians do not use health insurance at home. This also applies to students studying at Ukrainian universities. Instead, according to foreign experience, medical insurance is compulsory to study abroad at universities. This prompts entrants, who become students of European universities, to buy health insurance policies. It is clear that such insurance is preferable if the insurance company is chosen in the country of residence of the student. It is proposed to supplement the typology of financial flows of the insurance market by the category of “insurance cash flows”. The proposal is based on the fact that there are practically two streams of medical insurance for Ukrainian students studying abroad. There are two directions of the movement of funds: payment of insurance policies by insured persons and payment of insurance funds in the insurance case by the insurer. For each of these two streams, it is suggested to use the definition “insurance cash flows”. The methodological principles for conducting research are formulated. The indicators for calculations and comparison, as well as the composition of the initial data for calculations are determined. The calculation and comparison of the volumes of insurance flows connected with medical insurance of Ukrainian citizens studying at foreign universities of five countries is made. In particular, settlements for insurance terms of Austria, Bulgaria, Germany, Poland and the Czech Republic are made. The comparison is made in euro currency and hryvnia – the national currency of Ukraine.
Keywords: insurance; medical insurance; insurance cash flows; typology of insurance cash flows; volume of insurance cash flow; 368